Seven Steps of the Implementation of Mind Mapping Method in Learning of Islamic Education - Febriani, Afifah; Sindi, Nurul Fadila; Amanda, Loly Grenia; Rahman, Rina Aulia; Putri, Arsya Rahmanda (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2022)
The use of learning methods is needed in learning activities, with the existence of learning methods the process of delivering learning is more effective. This study aims to find out what the steps for implementing the mind mapping method in learning morality in junior high schools are. This study uses a qualitative method with a case study approach. Sources of data were taken from three informants through a set of interview protocols that have been validated by one expert in their field, the informant is a teacher of Islamic religious education in junior high schools. The informants were selected through a purposeful sampling technique. Then, all of the interview results are analyzed by using Milles and Huberman pattern. From the results of the interview, it was stated that the use of the mind mapping method consisted of seven steps, namely four steps taken by the teacher consisting of first providing media and learning resources, second delivering mind mapping material, third dividing students into several groups, fourth carrying out evaluation while three implementation steps the activities carried out by the students consisted of the first students discussing making a complete mind map, the second students presenting the results of the discussion in front of the class and the third students concluding the lesson. The results of this study can be used as initial data for further research in examining this problem in different contexts and issues.